Online Media Perspective on Trans Jogja as a Public Service in Yogjakarta City with Code Modeling - Astutik, Herna; Eriyanto Bayu Aji, Ganang (International Journal of Applied and Scientific Research, 2023)
Transjogya buses are currently not optimal. This research to analyze public perceptions of the importance of Transyogya buses as public  transportation in the Special Region of Yogyakarta. This research method uses qualitative research methods by collecting data from online news media, online magazines and other online news sources. The method used modelling coding is to use Nvivo12 software by capitalizing the code results to get analysis results. His research data, it can be seen that by analyzing the agenda setting teory which consists of the media agenda with an online media perspective, it shows that the problems that are often discussed by the mass media related to Transyogya Transportation are Bus Stop Problems, Transyogya Problems and Portable Bus Stop Problems.